Schimke immune-osseous dysplasia at the junction of specialties. A clinical case of disease diagnosis by allergologists and immunologists - E. S. Iljina; D. A. Veyler; P. D. Lashevich (Аллергология и Иммунология в Педиатрии, 2025)
Introduction. Schimke immuno-osseous dysplasia (SIOD) is an autosomal recessive, ultrarare disorder characterized by multisystem involvement accompanied by spondyloepiphyseal dysplasia of the skeleton, steroid-resistant proteinuric nephropathy leading to progressive loss of renal function, impaired immunity, and vascular damage caused by atherosclerosis. SIOD is caused by biallelic pathogenic variations in the SMARCAL1 gene.The clinical manifestations of SIOD are very diverse: from a rapidly progressive disease in which children die in the first years of life, to milder forms in which they survive to adulthood. The correlation between genotype and phenotype is extremely weak, so it is impossible to predict either the clinical course or the outcome of the disease. For this reason, patients with this pathology can be seen by various specialists.Case report. The publication presents a clinical case of a 4-year-old boy with immunological deficiency, developmental disorders, and skeletal anomalies, indicating in favor of SIOD.Whole exome sequencing in the SMARCAL1 gene revealed mutation variants с.2542G>T (p.Glu848Ter); c.1682G>T (p.Arg561Leu) in a heterozygous state.Based on the results of the genetic study, and also taking into account that the disease is multisystemic, the child was examined by a nephrologist, orthopedist, endocrinologist and geneticist.Conclusions of the nephrologist: glomerulopathy in Schimke syndrome: isolated proteinuria. Left calicectasis. Chronic kidney disease (CKD), stage 2. Glomerular filtration rate (Schwartz test) — 69.01 ml/min/1.73 m2.Endocrinologist’s conclusion: syndromic short stature. Protein-energy malnutrition grade 2.A telemedicine consultation was conducted with the Federal State Budgetary Institution National Medical Research Center for Pediatric Hematology and Oncology named after D. Rogachev, based on the results of which replacement therapy with intravenous or subcutaneous immunoglobulins was recommended, as well as hospitalization in the immunology department of this federal center.Conclusion. This description is the first case of diagnostics of an ultrarare disease (1:1–3,000,000 live births) in Krasnodar region by regional specialists. In this patient, the course of the disease is characterized by a non-severe, non-progressive renal dysfunction, which gives reason to assume a milder form of the disease. Conducting replacement therapy with immunoglobulins makes it possible to improve the prognosis in this patient.